Сommunicative approach as one of teaching method of Persian language - Akhmetova, F K; Gholamhosseinzadeh, G; Xodayar, E; Ameri, H (Journal of Oriental Studies, 2016)
In this article authors undertake attempts to increase efficiency of educational process on Persian language teaching of undergraduates by use of experience both teachers and students. Single issues on teaching of foreign language are presented and studied. A subject of study in this article is experience of Persian language teachers and students of Persian language who have already formed grammatical skills and abilities are already created, but not passed language training in the country of the studied language. Tasks are: formation of ideas of cultures variety of the training language country at trainees and assistance to trainees at self- studying of speech activity for the best assimilation and accustoming to Persian language and development of dialogical speech of trained undergraduates by means of communicative approach.